Lumbar Artery Pseudoaneurysm: A Complication of Percutaneous Nephrostomy - Melody Djuimo; Melanie Aubé; Mathieu Beland; Claudio Jeldres; Michel Carmel; Andrew Benko (Urology Case Reports, 2017)
A 21 year-old male underwent nephrostomy tube insertion for hydronephrosis due to a large para-aortic adenopathy of a testicular tumor. In order to reduce infections during chemotherapy, a ureteral stent was placed. While removing the nephrostomy tube, a pulsatile bleeding was found and a renal angiography was done. A pseudoaneurysm of his first left lumbar (L1) artery communicating with the nephrostomy's access site was found. An embolization was performed with coils in the left L1 artery and one of its subdivisions. Post-embolization controls revealed no bleeding. On the follow-up CT, there were no suspicious retroperitoneal mass.